Happiness is the only true emotion - Lambelet, Clément 1991-; Polli, Nicolas (RVB Books, 2019)
Database classification system: Anger, Disgust, Fear, Happiness, Neutral, Pain, Sadness, Surprise --Emotional index --Afterword: Emotions under glass --Postface: Des emotions sous verre